ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN ANTENATAL PADA IBU HAMIL TRIMESTER III DI UPTD PUSKESMAS LANGSA KOTA - Indah Dewi Sari; Dian Zuiatna; Cut Julia Andria (Jurnal Kesehatan dan Kedokteran, 2023)
Pregnancy check-up as one of the early prevention efforts from risk factors for pregnancy. The low coverage of K4 visits in Indonesia is as much as 74.1% of prenatal care in the third trimester. The aim of the study was to find out the factors associated with third trimester pregnancy checks at the UPTD Puskesmas Langsa City in 2021. This study used an analytic survey with a cross sectional approach. The population in this study were all third trimester pregnant women as many as 65 respondents. Data collection techniques using primary data. In this study using univariate and bivariate data analysis. The results of this study used the Pearson Chi-Square statistical test for third trimester antenatal visits on knowledge with a p-value of 0.000, education with a p-value of 0.168, employment with a p-value of 0.000, family support with a p-value of 0.000, information with a p-value 0.000. The conclusion in this study is that knowledge and support from family, work and information have a relationship with examination of third trimester pregnancy visits. This research suggests health workers to provide health information to increase knowledge about the importance of third trimester pregnancy visits.